Getting started with React VR : build immersive virtual reality apps for the web with React - Gwinner, John (Packt Publishing, 2017)
This book takes you on a journey to create intuitive and interactive Virtual Reality experiences by creating your first VR application using React VR 2.0.0. It starts by getting you up to speed with Virtual Reality (VR) and React VR components. It teaches you what Virtual Reality (VR) really is, why it works, how to describe 3D objects, the installation of Node.js (version 9.2.0) and WebVR browser. You will learn 3D polygon modeling, texturing, animating virtual objects and adding sound to your VR world. You will also discover ways to extend React VR with new features and native Three.js. You will learn how to include existing high-performance web code into your VR app. This book will also take you through upgrading and publishing your app. By the end of this book, you'll have a deep knowledge of Virtual Reality and a full-fledged working VR app to add to your profile!